2018
DOI: 10.1002/jso.25304
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of mismatch repair genes MLH1 and MSH2 is associated with chemotolerance of breast carcinoma: Clinical significance

Abstract: Background and Objectives: The aim of the study was to understand the importance of mismatch repair genes MLH1 and MSH2 in chemotolerance and prognosis of breast carcinoma (BC). Methods: First, the alterations (deletion/methylation/expression) of MLH1 and MSH2 were analyzed in 45 neoadjuvant chemotherapy (NACT)-treated and 133 pretherapeutic BC samples. The chemotolerant BC cells were characterized by treating two BC cell lines MCF-7 and MDA MB 231 with two anthracycline antitumor antibiotics, doxorubicin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The previously reported significant prognostic role of dMMR in TNBC (6,15) has not been confirmed by Ren et al because they found only 1 IHC dMMR and no MSI-H cases. In this respect, a study by our group focusing on MMR patterns of expression showed a better prognosis for TNBC tumors with MMR proteins perturbations (5).…”
Section: The Rationale For Mmr Clinical Testing In Tnbcmentioning
confidence: 81%
See 2 more Smart Citations
“…The previously reported significant prognostic role of dMMR in TNBC (6,15) has not been confirmed by Ren et al because they found only 1 IHC dMMR and no MSI-H cases. In this respect, a study by our group focusing on MMR patterns of expression showed a better prognosis for TNBC tumors with MMR proteins perturbations (5).…”
Section: The Rationale For Mmr Clinical Testing In Tnbcmentioning
confidence: 81%
“…The previously reported significant prognostic role of dMMR in TNBC ( 6 , 15 ) has not been confirmed by Ren et al. because they found only 1 IHC dMMR and no MSI-H cases.…”
Section: The Rationale For Mmr Clinical Testing In Tnbcmentioning
confidence: 82%
See 1 more Smart Citation
“…The assembly will initiate endonuclease activity of PMS2 which createssingle-strand breaks close to the mismatch and allows for the removal of thewrong-inserted base by exonuclease 1 (EXO1) seems to be more frequent [31]. Several studies confirmed that MMR deficiency is significantly associated with an increased risk of death in breast cancers, particularly in the HR+ group [21,29,32]. Despite this recognized prognostic role, the predictive value of MMR alterations is still controversial in these tumors [33].…”
Section: Frequency and Specific Pathways Involvedmentioning
confidence: 99%
“…Upstream regulators control BRCA tumor growth [20]. However, MLH1/MSH2, methylation product of the DNMT gene may be important for the chemotherapeutic tolerance of BRCA [21,22].…”
Section: Introductionmentioning
confidence: 99%